DIGITALIZATION OF ISLAMIC BANKING - Fero Arum Cahyani; Mirnawati; Muhammad Misbakul Munir (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Digitalization of the Islamic economy can enter various parts of the economy, both macro and micro. Today, digital technology plays a tremendous role in almost every economy. Digitalization is also known as information and communication technology that is used in product packaging and marketing so that information is more easily and quickly distributed. The information is then used to support and accelerate economic growth enabled by digital and information technology. The era of digitalization of information and communication can help both conventional and Islamic economies because information technology has entered into the lives of individuals. Gadget users can now access this technology through mobile applications that have easy-to-understand and downloadable functions. Similarly, in the banking industry, Islamic banking is working with the information technology industry to build a better information system. This application is intended to simplify the entire banking transaction process. The emergence of a digital society is due to the rapid increase and spread of information and communication technology in all sectors, including marketing, economics, finance, services, education, and others. Therefore, digitalization was created to ease user transactions and improve the economy.